A rare case of systemic lupus erythematosus presenting with concurrent myocarditis, central retinal vein occlusion, and deep vein thrombosis - Mehrdad Jafari Fesharaki; Negar Raissi Dehkordi; Zahra Zakeri; Emadoddin Hosseinjani; Nastaran Raissi Dehkordi (Clinical Case Reports)
Key Clinical Message Although systemic lupus erythematosus may present with broad and variable symptoms, the rare and atypical combined presentation of central retinal vein occlusion, myocarditis, and deep vein thrombosis poses a diagnostic challenge and highlights the need for a comprehensive diagnostic approach. Early diagnosis and prompt treatment help mitigate disease morbidity and mortality, and emphasize the importance of heightened clinical suspicion in complex presentations.